Reducing Sedentary Time and Whole-Body Insulin Sensitivity in Metabolic Syndrome - A 6-Month Randomized Controlled Trial - Sjöros Tanja; Laine Saara; Garthwaite Taru; Vähä-Ypyä Henri; Löyttyniemi Eliisa; Koivumäki Mikko; Houttu Noora; Laitinen Kirsi; Kalliokoski Kari K.; Sievänen Harri; Vasankari Tomi; Knuuti Juhani; et al. (United States, 2025)
Purpose: To investigate whether a reduction in daily sedentary behavior (SB) improves insulin sensitivity in adults with metabolic syndrome in 6 months, without adding intentional exercise training.
Methods: Sixty-four sedentary inactive middle-aged adults with overweight and metabolic syndrome [mean age 58 (SD 7) years, mean BMI 31.6 (SD 4.3) kg/m2; 27 men] were randomized into intervention and control groups. The 6-month individualized behavioral intervention supported by an interactive accelerometer and a mobile application aimed at reducing daily SB by 1 h compared to baseline. Insulin sensitivity by hyperinsulinemic euglycemic clamp, body composition by air displacement plethysmography and fasting blood samples were analyzed before and after the intervention. SB and physical activity were measured with hip-worn accelerometers throughout the intervention.
Results: SB decreased by 40 (95%CI 17-65) min/day and moderate-to-vigorous physical activity increased by 20 (95%CI 11-28) min/day on average in the intervention group with no significant changes in these outcomes in the control group. After 6 months, fasting plasma insulin decreased (~1 mU/L) in the intervention group compared to the control group (time*group p = 0.0081), but insulin sensitivity did not change in either group. The changes in body mass or adiposity did not differ between groups. Among all participants, the changes in SB and body mass correlated inversely with the change in insulin sensitivity (r = -0.31, -0.44; p = 0.025, 0.0005; respectively).
Conclusions: An intervention aimed at reducing daily SB resulted in slightly decreased fasting insulin, but had no effects on insulin sensitivity or body adiposity. However, as the change in insulin sensitivity associated with the changes in SB and body mass, multifaceted interventions targeting to weight loss are likely to be beneficial in improving whole-body insulin sensitivity.